2016
DOI: 10.1002/pssc.201600062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of holding time on the size distribution of β‐Si3N4 particles and nucleation undercooling in multicrystalline silicon

Abstract: The nucleation mechanism for directional solidification of multicrystalline silicon (mc‐Si) in silicon nitride (Si3N4) coated crucibles has been investigated. A combination of thermal and particle size analysis was used to show that the nucleation undercooling was inversely proportional to the particles size. The particle size was increased by keeping the silicon melted for increasing time periods and the growing particles were identified as β‐Si3N4. The results from the particle analysis were verified by topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The main difference between the samples from the different groups is that one requires a nucleation phase prior to initial growth, while the second does not, and the nucleation requires a supercooling. Several groups have measured the supercooling of silicon melt on silicon nitride powder coating before nucleation [20][21][22], and the results vary between 0 and 40 K. However, it has been shown that the α-silicon nitride polymorph of which this coating is predominantly made is transformed to β-polymorph upon contact with silicon melt, which is accompanied by an increase in particle size [13,22]. The more recent of the studies which account for this reaction report a supercooling in the range of 0 to 10 K. The minimum supercooling required to initiate faceted dendritic growth in a silicon melt is was reported by Fujiwara et al to be 10 K [23].…”
Section: Mechanisms Controlling Grain Boundary Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference between the samples from the different groups is that one requires a nucleation phase prior to initial growth, while the second does not, and the nucleation requires a supercooling. Several groups have measured the supercooling of silicon melt on silicon nitride powder coating before nucleation [20][21][22], and the results vary between 0 and 40 K. However, it has been shown that the α-silicon nitride polymorph of which this coating is predominantly made is transformed to β-polymorph upon contact with silicon melt, which is accompanied by an increase in particle size [13,22]. The more recent of the studies which account for this reaction report a supercooling in the range of 0 to 10 K. The minimum supercooling required to initiate faceted dendritic growth in a silicon melt is was reported by Fujiwara et al to be 10 K [23].…”
Section: Mechanisms Controlling Grain Boundary Densitymentioning
confidence: 99%
“…This will explain the higher concentration of twins as well as Σ27 through branching of the dendrites. In conclusion, to control the density of twins and CSL boundaries in the non-seeded method, coating morphology is of no consequence; here, the supercooling has to be reduced by means of controlling the structure and size of the particles on which nucleation occurs, as described in the works of Ekstrøm [13] and Undheim [22,24]. It is interesting to see that this conclusion is corroborated by the observation of Brynjulfsen that coating parameters, including roughness, did not influence the supercooling [21].…”
Section: Mechanisms Controlling Grain Boundary Densitymentioning
confidence: 99%
“…The β-phase particles grow to much larger sizes than the α-phase particles in the original coating, on the order of 10-20 μm [2]. Our work shows that the larger β-particles are more favorable nucleation sites than the α-Si3N4 particles [1,2].…”
Section: Introductionmentioning
confidence: 66%
“…The nitride coating commonly used by mc-Si producers is composed of mainly α-Si3N4 (> 95%) and small amounts of β-Si3N4 particles. The particles in this coating are small, with a size below 1 μm [1].…”
Section: Introductionmentioning
confidence: 99%